2020
DOI: 10.1021/acs.nanolett.0c03357
|View full text |Cite
|
Sign up to set email alerts
|

Pt/AlGaN Nanoarchitecture: Toward High Responsivity, Self-Powered Ultraviolet-Sensitive Photodetection

Abstract: Energy-saving photodetectors are the key components in future photonic systems and particularly, self-powered photoelectrochemical-type photodetectors (PEC-PDs) which depart completely from the classical solid-state junction device, have lately intrigued intensive interest to meet next-generation power-independent and environment-sensitive photodetection. Herein, we construct, for the first time, solar-blind PEC PDs based on self-assembled AlGaN nanostructures on silicon. Importantly, with the proper surface p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
139
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 70 publications
3
139
1
Order By: Relevance
“…In recent years, the mainly used materials for preparing VUV detectors are those naturally ultrawide-bandgap semiconductor materials such as AlN [12][13][14], AlGaN [15][16][17] and BN [18][19][20][21][22]. Gallium oxide (Ga 2 O 3 ) is also considered to be a candidate for VUV detection, by adding aluminum component to obtain (AlGa) 2 O 3 ternary sesquioxides with a freely-adjustable bandgap (4.9-8.8 eV).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the mainly used materials for preparing VUV detectors are those naturally ultrawide-bandgap semiconductor materials such as AlN [12][13][14], AlGaN [15][16][17] and BN [18][19][20][21][22]. Gallium oxide (Ga 2 O 3 ) is also considered to be a candidate for VUV detection, by adding aluminum component to obtain (AlGa) 2 O 3 ternary sesquioxides with a freely-adjustable bandgap (4.9-8.8 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Research in wide-bandgap III-nitride semiconductors continues to progress rapidly, especially for the materials with bandgap exceeding that of gallium nitride (3.4 eV). Specifically, III-nitride based heterostructures provide new opportunities for a wide range of research and device applications, such as piezotronics and piezophototronics [1], self-powered photoelectrochemical-type photodetectors [2], room-temperature quantum emitters [3], single photon emitters [4][5][6], resonant tunneling diodes [7], highelectron-mobility transistors [8,9], efficient photoelectrocatalysts for solar water splitting [10], multi-wavelength light-emitting diodes (LEDs) [11,12], and deep ultraviolet (DUV)-LEDs [13][14][15][16][17]. AlGaN-based DUV-LEDs represent a sustainable alternative to replace the environmentally harmful conventional mercury lamps [18] and thus, are becoming crucial for many applications such as water purification and/or inactivation of microorganisms, including bacteria, fungi, and viruses [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…MSM geometry includes back-to-back metal semiconductor (MS) contacts where the same metal electrodes are defined as symmetrical MSM and different metal electrodes are defined as asymmetrical MSM device. S. Chang [13][14][15]. At the same time, H. Sun et al also reported a GaN/AlGaN HEMT with a peak photoresponsivity of 6×10 7 A/W [16].…”
Section: Introductionmentioning
confidence: 99%